2002
DOI: 10.1023/a:1020158631102
|View full text |Cite
|
Sign up to set email alerts
|

Phenylketonuria in adulthood: A collaborative study

Abstract: During 1967-1983, the Maternal and Child Health Division of the Public Health Services funded a collaborative study of 211 newborn infants identified on newborn screening as having phenylketonuria (PKU). Subsequently, financial support was provided by the National Institute of Child Health and Human Development (NICHD). The infants were treated with a phenylalanine (Phe)-restricted diet to age 6 years and then randomized either to continue the diet or to discontinue dietary treatment altogether. One hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 187 publications
(76 citation statements)
references
References 13 publications
2
72
1
1
Order By: Relevance
“…Depression is one of the common symptoms in adult off-diet PKU patients3334; however, biochemical linkage of the blood phenylalanine level to the depression state has not been resolved. Recent studies in depression have demonstrated that the reduced cerebral protein synthesis, which is also reported in PKU patients with elevated plasma phenylalanine35, is due to low mTORC activity in neuronal cells36.…”
Section: Discussionmentioning
confidence: 99%
“…Depression is one of the common symptoms in adult off-diet PKU patients3334; however, biochemical linkage of the blood phenylalanine level to the depression state has not been resolved. Recent studies in depression have demonstrated that the reduced cerebral protein synthesis, which is also reported in PKU patients with elevated plasma phenylalanine35, is due to low mTORC activity in neuronal cells36.…”
Section: Discussionmentioning
confidence: 99%
“…Poor dietary control results in high plasma Phe-concentrations, which lead to neurocognitive impairment and negatively affect attention span, mood [4] and cognitive performance [5]. Consequently, lifelong dietary therapy with good metabolic control is recommended [6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, adults with PKU who continued diet performed at a level comparable to genetic expectations as measured by their parents' IQ. 8 High Phe levels are known to be toxic for the fetal brain, as the main consequences of maternal PKU are microcephaly and mental retardation. 9 However, no clear data are available about the effect of high Phe in the brain of premature babies and especially about blood threshold Phe concentrations and/or duration of high Phe levels on clinical outcome of these patients.…”
Section: Introductionmentioning
confidence: 99%